Chapitre 3 : étiages et sécheresses = Chapter 3 : low flows and droughts - (:unkn) unknown (My University, 1997)
These two dimensions (low flows and droughts) are addressed within the set of five papers presented in this chapter. Three of the five presented papers summarise work undertaken within three regional FRIEND group : low flow regimes in Western Europe ; regional water resources and drought assessment in Southern African ; long-term effects of rain-shortage in West and Central Africa. Two other papers summarise work undertaken in the Alpine-Mediterranean region, during the recent introductory phase of this topic : drought in South-Eastern Europe ; statistical analysis of low flows with zero discharge.
Keywords: African Research